Cytomegalovirus Enterocolitis in a Patient Treated with Methylprednisolone for Amiodarone Hypersensitivity Pneumonitis - Darinka Purg; Marko Hojnik; Nika Aleksandra Kravos Tramšek (Diagnostics)
Cytomegalovirus (CMV) is a common cause of infection in immunocompromised individuals, such as patients with hematological malignancies or AIDS, but can also occur in patients with other acquired immunodeficiencies. In tissue-invasive diseases, CMV diagnosis requires CMV DNA in the plasma and the histological confirmation of CMV in a tissue or organ. Evidence of CMV colitis requires a characteristic endoscopic picture with ulcers with a well-defined, convex appearance and CMV viral inclusions in the form of an “owl’s eye” on mucosal sections stained with hematoxylin and eosin. CMV-specific immunohistochemistry is the gold standard for identifying CMV in tissue biopsies. It is important to consider a CMV infection in the diagnostic process, as it may delay the diagnosis and the treatment. We present the case of a 78-year-old patient with amiodarone interstitial lung disease who was treated with methylprednisolone. Two weeks after the start of his treatment, he was admitted to the hospital for acute gastroenterocolitis and Addisonian crisis. An examination had confirmed a tissue-invasive CMV disease. He was treated with valganciclovir for a total of six weeks. After the completion of treatment, the patient showed no clinical signs of CMV infection, and both laboratory and histological examinations revealed no residual CMV disease. Tissue-invasive CMV disease can occur in patients with acquired immunodeficiency, which may result from various causes, including glucocorticoid treatment.